1998
DOI: 10.1021/bi9729357
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a New Substrate-Derived Radical during Inactivation of Ribonucleotide Reductase from Escherichia coli by Gemcitabine 5‘-Diphosphate

Abstract: Ribonucleotide reductases (RNRs) play a central role in replication and repair by catalyzing the conversion of nucleotides to deoxynucleotides. Gemcitabine 5'-diphosphate (F2CDP), the nucleoside of which was recently approved by the FDA for treatment of pancreatic cancer, is a potent mechanism-based inhibitor of class I and II RNRs. Inactivation of the Eschericia coli class I RNR is accompanied by loss of two fluorides and one cytosine. This RNR is composed of two homodimeric subunits: R1 and R2. R1 is the sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 34 publications
3
74
1
Order By: Relevance
“…Unlike ara-C, gemcitabine has a second mechanism of action that contributes to cytotoxicity. The diphosphate of gemcitabine (dFdCDP) serves as an inhibitory alternative substrate for ribonucleotide reductase and inactivates this key enzyme in a mechanism-based manner, which leads to a decrease in deoxynucleotide pools (Baker et al, 1991;van der Donk et al, 1998;Wang et al, 2007). The change in the dFdCTP:CTP ratio likely leads to enhanced gemcitabine incorporation and further DNA synthesis inhibition, an action known as self-potentiation (Heinemann et al, 1990(Heinemann et al, , 1992.…”
Section: Targeting Dna Replicationmentioning
confidence: 99%
“…Unlike ara-C, gemcitabine has a second mechanism of action that contributes to cytotoxicity. The diphosphate of gemcitabine (dFdCDP) serves as an inhibitory alternative substrate for ribonucleotide reductase and inactivates this key enzyme in a mechanism-based manner, which leads to a decrease in deoxynucleotide pools (Baker et al, 1991;van der Donk et al, 1998;Wang et al, 2007). The change in the dFdCTP:CTP ratio likely leads to enhanced gemcitabine incorporation and further DNA synthesis inhibition, an action known as self-potentiation (Heinemann et al, 1990(Heinemann et al, , 1992.…”
Section: Targeting Dna Replicationmentioning
confidence: 99%
“…The monophosphate of F 2 C (F 2 CMP) is generated by deoxycytidine kinase (7) and is rapidly phosphorylated to the di-and triphosphates (F 2 CDP and F 2 CTP) (8,9). Diphosphorylated F 2 C (F 2 CDP) is an irreversible inhibitor of ribonucleotide reductase (RNR) (10)(11)(12)(13), and F 2 CTP functions as a chain terminator in the DNA polymerase reaction (14,15). Differentially phosphorylated states of gemzar can also interfere with other enzymes involved in nucleotide metabolism.…”
mentioning
confidence: 99%
“…A number of years ago, we reported on the inactivation of E. coli RNR by F 2 CDP (11,12). We showed that 1 eq of F 2 CDP per E. coli RNR, presumably ␣ 2 ␤ 2 , in the presence of reductants, thioredoxin (TR) and TR reductase or DTT, is sufficient for enzyme inactivation and that the inactivation is accompanied by release of 2 fluoride ions and one cytosine (12).…”
mentioning
confidence: 99%
“…However, no detection of the furanone at 320 nm was observed like most 2'-substituted nucleotides during the inactivation. 39,51 Instead, formation of a new stable substrate derived radical was detected as a triplet EPR signal at 9 GHz during the inhibition of RNR by Gemcitabine. 51 Moreover, unlike other 2'-substituted nucleotides that require the presence of reductants (namely cysteine residues C754 and C759 and NADPH) for the inhibition, the presence or absence of reductants did not affect the inhibitory action of Gemcitabine.…”
Section: Inhibition Of Ribonucleotide Reductases By Other 2'-substitumentioning
confidence: 99%
“…39,51 Instead, formation of a new stable substrate derived radical was detected as a triplet EPR signal at 9 GHz during the inhibition of RNR by Gemcitabine. 51 Moreover, unlike other 2'-substituted nucleotides that require the presence of reductants (namely cysteine residues C754 and C759 and NADPH) for the inhibition, the presence or absence of reductants did not affect the inhibitory action of Gemcitabine. Inhibition in the presence of the reducing system happened through covalent labeling, which increased interaction between the two subunits.…”
Section: Inhibition Of Ribonucleotide Reductases By Other 2'-substitumentioning
confidence: 99%